Nano-Medicines a Hope for Chagas Disease! - Choudhury, Satabdi Datta (Frontiers in Molecular Biosciences, 2021)
Chagas disease, a vector-borne tropical disease whose causative agent is a protozoan parasite named Trypanosoma cruzi.It is one of the major public health problems in South America and Mexico infecting over 6 million people every year. Protozoan T. cruzi gets transmitted to human through Triatominae, a subfamily of the Reduviidae, and do not have any effective treatment or preventative available. Owing to the lack of economic gains from this tropical parasitic infection, it has always been neglected by researchers and drug manufacturers for many decades. Hence there is an immense need for more effective innovative strategies to decrease the deaths associated with these diseases. Even, available diagnosis protocols are outdated and inefficient and there is an urgent need for rapid high throughput diagnostics as well as management protocol. Recent advancement of nanotechnology in the field of healthcare has generated hope for better management of many tropical diseases including Chagas disease. Nanoparticulate systems for drug delivery like poloxamer coated nanosuspension of benzidazole has shown promising results in reducing toxicity, elevating efficacy and bioavailability of the active compound against the pathogen, by prolonging release, thereby increasing the therapeutic index. Moreover, nanoparticle-based drug delivery has shown promising results in inducing the host's immune response against the pathogen with very few side effects. Besides, advances in diagnostic assays, such as nanobiosensors, aided in accurate identification of the pathogen. In this review, we provide an insight into the life cycle stages of the pathogen in both vertebrate host and the insect vector, along with an overview of the current therapy for Chagas disease and its limitations; nano carrier-based delivery systems for antichagasic agents, we also address the advancement of nano vaccines and nanodiagnostic techniques, for treatment of Chagas disease, majorly focusing on the novel perspectives in combating the disease.